Application electromagnetic field of ultrahigh frequency for grain drying processes - Bilyk, S.; Bunko, V.; Marysyuk, A. (Енергетика і автоматика, 2015)
The influence of high frequency activation of the intensification of its grain drying active ventilation. The influence of various parameters on moisture diffusion coefficient, investigated the possibility of using thermocouples in the microwave field with determination temperature in the range of the microwave.